Response of Complete Fertilization Based on Nutrient Index to Improve Rice (Oryza sativa L.) Growth : Respon Pemupukan Lengkap Berdasarkan Indeks Gizi Terhadap Peningkatan Pertumbuhan Padi (Oryza sativa L.) - Henderlan Harahap, Lutfi (UPMI Proceeding Series, 2023)
Fertilizer is one of the main sources to increase the growth of rice plants. Provision of fertilizers in accordance with the vegetative and generative needs of rice plants will be able to increase the vegetative growth of rice plants, to see how the nutrients needed by rice plants are sufficient or not can be seen by the soil nutrient index so that fertilization effectiveness can be achieved. The purpose of this study was to provide N,P,K,Mg fertilizer doses according to the vegetative and generative needs of the plants and to see the soil reaction by looking at the nutrient index. The design of this experimental study was a factorial Completely Randomized Design (CRD) with 2 factors and 3 replications. The first factor is the complete application of Urea, SP-36, Kcl, and dolomite fertilizer consisting of: 0 g/plot; 549.574 g/plot; 824.36 g/plot; 1099.15 g/plot; 1373.94 g/plot. The second factor is the soil nutrient index consisting of: 0.9 (dose reduced by 10%); 1 (Standard nutrient index); 1.1 (Dose of fertilizer plus 10%) . The results showed that the application of fertilizer based on the nutrient index had a significant effect on the growth of plant height and the number of rice tillers. The addition of fertilizer in high doses of 1373.94 g/plot was able to produce a maximum growth of 101.73 cm/plot and the number of tillers was 55.52 stems/plot. The results of the research on the interaction between fertilizer doses and soil nutrient index combinations were best found in the P4B2 treatment on plant height and P4B1 on the number of tillers.